Reasonable Suspicion and Mere Hunches - Lerner, Craig S. (2006)
In Terry v. Ohio, Earl Warren held that police officers could temporarily detain a suspect, provided that they relied upon specific, reasonable inferences, and not simply upon an inchoate and unparticularized suspicion or 'hunch. ' Since Terry, courts have strained to distinguish reasonable suspicion, which is said to arise from the cool analysis of objective and particularized facts, from mere hunches, which are said to be subjective, generalized, unreasoned and therefore unreliable. Yet this dichotomy between facts and intuitions is built on sand. Emotions and intuitions are not obstacles to reason, but indispensable heuristic devices that allow people to process diffuse, complex information about their environment and make sense of the world. The legal rules governing police conduct are thus premised on a mistaken assumption about human cognition. This Article argues that the legal system can defer, to some extent, to police officers' intuitions without undermining meaningful protections against law enforcement overreaching. As a practical matter, the current legal regime substitutes palliative euphemisms for useful controls on police discretion. It forces police officers to prune what they say at suppression hearings, but it does little to change how they act on the streets of America. When an energetic police officer has a hunch that evil is stirring and action is imperative, the officer will simply act. Months will pass before a suppression hearing, and by then it will be a simple matter to reverse-engineer the objective reasons for the stop - e.g., I saw a bulge, or He made a furtive gesture. The legal system in practice rewards those officers who are able and willing to spin their behavior in a way that satisfies judges, while it penalizes other officers who are less verbally facile or who are transparent about their motivations. Politically accountable authorities should join the courts in monitoring police practices. And the focus should be less on what police say after the fact and more on what they do - that is, how successful police officers are in detecting criminals relative to the number of stops they make and how respectful officers are of all citizens